Proposal for a 2.0 knowledge management model for "Medellin, cluster city (Medellin, city of knowledge) (2011)
According to studies conducted in emerging economies, clusters are defined as strategies leading to power regional economic growth processes around the globe. This happens through knowledge creation, appropriation, transfer and distribution. Agents belonging to diverse sectors are involved into clusters such as the governmental sector, private, gild, entrepreneurial and the educational. Clusters are nowadays a fundamental tool to stimulate entrepreneurial growth in cities since it strengthens competitiveness in the regions and in the economies. Clusters allow companies from a certain sector to build business networks; spot new trade niches and become more competitive and more sustainable. As a top priority of its strategic plan of development, Medellin has given emphasis to the project "Medellin, a Cluster City". This project makes part of a bigger plan called "Medellin, City of Knowledge". Setting up and supporting clusters demand from the city proper knowledge infrastructure which leads it to achieve diverse objectives; objectives aiming at creating innovation, a chrysalis adapted to the city's context. This article presents a knowledge transfer model supported by Web 2.0 platforms which assists collaboration and interaction (generating associativity and cooperation) as fundamental components of clusters. Under these approaches and the supportive technologies, collective intelligence is expected to surge. The knowledge transfer model is based on Nonaka and Takeuchi's knowledge creation model.